2011
DOI: 10.1038/mp.2011.158
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental and neuropsychiatric behaviour defects arise from 14-3-3ζ deficiency

Abstract: Complex neuropsychiatric disorders are believed to arise from multiple synergistic deficiencies within connected biological networks controlling neuronal migration, axonal pathfinding and synapse formation. Here, we show that deletion of 14-3-3ζ causes neurodevelopmental anomalies similar to those seen in neuropsychiatric disorders such as schizophrenia, autism spectrum disorder and bipolar disorder. 14-3-3ζ-deficient mice displayed striking behavioural and cognitive deficiencies including a reduced capacity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
110
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 68 publications
9
110
3
Order By: Relevance
“…Several studies have shown that the isoform14-3-3ζ has an association with schizophrenia and related neurodevelopmental disorders on the gene- (Jia et al, 2004;Fromer et al, 2014;Toma et al, 2014), gene expression- (Middleton et al, 2005;Wong et al, 2005), and protein level (Sivagnanasundaram et al, Pharmacology, Biochemistry andBehavior 138 (2015) 1-8 2007;English et al, 2009;Focking et al, 2011;Schubert et al, 2015). We found that 14-3-3ζ KO mice display several schizophrenia-like behavioural deficits such as hyperactivity and disrupted sensorimotor gating, impaired novel object recognition, impaired learning in a water crossmaze escape task, and lower levels of anxiety in the elevated plus maze (Cheah et al, 2012). As previously reported, we found that clozapine ameliorated hyperactivity in 14-3-3ζ KO mice (Ramshaw et al, 2013).…”
Section: Introductionmentioning
confidence: 89%
“…Several studies have shown that the isoform14-3-3ζ has an association with schizophrenia and related neurodevelopmental disorders on the gene- (Jia et al, 2004;Fromer et al, 2014;Toma et al, 2014), gene expression- (Middleton et al, 2005;Wong et al, 2005), and protein level (Sivagnanasundaram et al, Pharmacology, Biochemistry andBehavior 138 (2015) 1-8 2007;English et al, 2009;Focking et al, 2011;Schubert et al, 2015). We found that 14-3-3ζ KO mice display several schizophrenia-like behavioural deficits such as hyperactivity and disrupted sensorimotor gating, impaired novel object recognition, impaired learning in a water crossmaze escape task, and lower levels of anxiety in the elevated plus maze (Cheah et al, 2012). As previously reported, we found that clozapine ameliorated hyperactivity in 14-3-3ζ KO mice (Ramshaw et al, 2013).…”
Section: Introductionmentioning
confidence: 89%
“…Several previous transcriptomic and proteomic analyses have identified alterations in 14-3-3 protein isoforms in postmortem tissue of people with schizophrenia and bipolar disorder (Altar et al, 2009;English et al, 2011), and genetic association with these disorders has been reported (Grover et al, 2009;Jia et al, 2004;Wong et al, 2005). Mice lacking the isoform 14-3-3ζ display significant deficits in hippocampus-dependent functions such as working memory, sensory gating, and associative learning (Cheah et al, 2012;Qiao et al, 2014) and these changes are associated with decreased levels of NMDA receptors in the postsynaptic density (PSD) of CA1 pyramidal neurons, leading to deficits in hippocampal long-term synaptic plasticity (Qiao et al, 2014).…”
Section: -3-3 Signalingmentioning
confidence: 99%
“…Dysfunction implicated in Angelman syndrome [49,50] CaMKII: Encodes a calcium/calmodulin-activated protein kinase. CaMKII immunoreactivity is most highly concentrated in the mushroom body lobes and calyces [51] 14-3-3z: Encodes 14-3-3 proteins necessary for neurodevelopment and social cognition [52] leo: Encodes 14-3-3z orthologue Leonardo, enriched in mushroom bodies and necessary for olfactory learning and memory [53] rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Introductionmentioning
confidence: 99%